Isolated Third, Fourth, and Sixth Cranial Nerve Palsies in the Turkish Population: Etiologic Factors and Clinical Course - Ayşe İlksen Çolpak; Hale Batur Çağlayan (Türk Nöroloji Dergisi, 2019)
Objective: To determine the etiologic factors and clinical profile of isolated third, fourth, and sixth nerve palsies in neuro-ophthalmology outpatient clinics of two different reference centers. Materials and Methods: Retrospective evaluation of medical records from the institutional database. Results: A total of 127 (78 male, 49 female) patients were analyzed. Forty-five (35.4%) patients had isolated third nerve palsy, 34 (26.8%) had isolated fourth nerve palsy, and 48 (37.8%) patients had isolated sixth nerve palsy. The mean ages were similar; 58.87±13.6, 56.32±16.1, and 54.9±14.4 years, respectively (p=0.4). Diplopia was the main symptom seen in all patients. Twenty-one patients had anisocoria (20 third, 1 fourth). Among patients with anisocoria, 3 patients had final diagnoses of vasculopathy, the rest were diagnosed as having acquired non travmatic palsy with different etiologies such as aneurysm, Tolosa-Hunt syndrome, and carotico-cavernous fistula. The most common etiology for all groups was vasculopathy. Three patients with isolated oculomotor nerve palsy were diagnosed as having Tolosa-Hunt sydnrome despite pupillary sparing. The mean recovery time was similar for all cranial nerve palsies. Conclusion: Although, the most common etiology of third, fourth, and sixth nerve palsies is vasculopathy, neuroimaging studies are crucial to exclude potentially treatable and dangerous conditions.